Back cover: Immunoproteomics of Aspergillus for the development of biomarkers and immunotherapies. Issue 9 (October 2016) - Kniemeyer, Olaf; Ebel, Frank; Krüger, Thomas; Bacher, Petra; Scheffold, Alexander; Luo, Ting; Strassburger, Maria; Brakhage, Axel A.
Abstract : DOI:10.1002/prca.201600053 Representatives of the genus Aspergillus are known as pathogenic moulds which can cause a diverse spectrum of human pulmonary diseases. The adaptive immune system plays a critical role for controlling Aspergillus infections. Immune proteomic methods (here exemplarily illustrated by a 2D immunoblot) can contribute to the development of diagnostic tools or a vaccine. Further details can be found in the article by Olaf Kniemeyer et al. on page 910.